Dual Band Antenna for Wi-Fi and 5G Communication - Meor Said, Maizatul Alice; Misran , Mohamad Harris; Othman, Mohd Azlishah; Jaafar, Abd Shukur; Abd Manap, Redzuan; Suhaimi, Shadia; Hassan, Nurmala Irdawaty (Journal of Science and Technology, 2024)
The objective of this project is to design a microstrip antenna that operates in both the Wi-Fi and 5G frequency bands, specifically at 2.4GHz for Wi-Fi and 3.5GHz for 5G communication. The antenna design pattern on a FR4 substrate has been selected to be a rectangular microstrip patch antenna due of its low-profile form. The square patch antenna incorporates slot and inset feed techniques to achieve dual band operation and improve antenna performance. The antenna operates at the resonant frequencies of 2.4GHz and 3.5GHz. The S11 values at these frequencies are -19.948dB and -26.151dB, respectively. The antenna’s gain is 2.698dB at 2.4GHz and 1.359dB at 3.5GHz. The antenna design was simulated using CST Microwave Studio, and the measurements were conducted using a Vector Network Analyzer (VNA).